Traditional knowledge in semi-rural close to industrial areas: ethnobotanical studies in western Gironès (Catalonia, Iberian Peninsula) - Airy Gras; Ginesta Serrasolses; Joan Vallès; Teresa Garnatje (BMC, 2019)
Abstract Background The western Gironès is a district located in NE Catalonia (NE Iberian Peninsula). This area comprising 186.55 km2 and 10,659 inhabitants is composed of 5 municipalities encompassing 29 villages, located in the hydrographic basins of the Ter and Llémena rivers. Methods Following the methodology based on the semi-structured interviews, we carried out 40 interviews with 57 informants, 31 were women and the remaining 26 were men, with an average age of 78.6 years. Results In the present study, data from 316 taxa (301 angiosperms, 8 gymnosperms, and 7 pteridophytes) belonging to 89 botanical families were collected. The interviewed informants referred 3776 UR of 298 taxa, 1933 (51.19%) of them corresponding to the food category, 949 (25.13%) to the medicinal ones, and 894 (23.68%) to other uses. In addition, 581 vernacular names for 306 species, subspecies, and varieties have also been collected. Conclusions These results reveal the validity of traditional knowledge in the studied area, which can be seriously threatened by the loss of its rural condition and its proximity to industrialized areas.